2009
DOI: 10.3177/jnsv.55.31
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Sesame Lignans (Sesamin, Episesamin and Sesamolin) Affecting Gene Expression Profile and Fatty Acid Oxidation in Rat Liver

Abstract: SummaryThe impact of sesamin, episesamin and sesamolin (sesame lignans) on hepatic gene expression profiles was compared with a DNA microarray. Male Sprague-Dawley rats were fed experimental diets containing 0.2% sesamin, episesamin or sesamolin, and a control diet free of lignans for 15 d. Compared to a lignan-free diet, a diet containing sesamin, episesamin and sesamolin caused 1.5-and 2-fold changes in the expression of 128 and 40, 526 and 152, and 516 and 140 genes, respectively. The lignans modified not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 32 publications
6
42
0
Order By: Relevance
“…The biological effects of sesamin and episesamin were compared previously (Kushiro et al, 2002;Ide et al, 2009). Kushiro et al (2002) demonstrated that episesamin was much stronger at increasing the activity and gene expression of the enzymes involved in fatty acid oxidation in the liver of rats fed 0.2% of sesamin or episesamin for 15 days.…”
Section: Introductionmentioning
confidence: 99%
“…The biological effects of sesamin and episesamin were compared previously (Kushiro et al, 2002;Ide et al, 2009). Kushiro et al (2002) demonstrated that episesamin was much stronger at increasing the activity and gene expression of the enzymes involved in fatty acid oxidation in the liver of rats fed 0.2% of sesamin or episesamin for 15 days.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to sesamin, sesamolin and episesamin had a much stronger effect on fatty acid oxidation and miscellaneous genes involved in fatty acid transport and metabolism, except for those involved in lipogenesis 15 . However, the present observation showed that seeds from ME variety, which contained fat-soluble lignan predominantly as sesamin and was almost devoid of sesamolin, was as effective as seeds from GZ and MH varieties, which contained sesamin and sesamolin at about a 2:1 ratio, in affecting the parameter of hepatic fatty acid oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been indicated that Cd36 38 and carnitine transporter genes 39 are under the control of PPARα. We previously observed that fat-soluble lignans increased the mRNA expression of Cd36, a transporter involved in fatty acid uptake, and carnitine transporter 15 . Therefore, it is conceivable that these changes represent the consequence of PPARα activation by the lignans contained in sesame seeds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations